2019
DOI: 10.1530/joe-18-0455
|View full text |Cite
|
Sign up to set email alerts
|

Fetal hyperglycemia acutely induces persistent insulin resistance in skeletal muscle

Abstract: Offspring exposed in utero to maternal diabetes exhibit long-lasting insulin resistance, though the initiating mechanisms have received minimal experimental attention. Herein, we show that rat fetuses develop insulin resistance after only 2-day continuous exposure to isolated hyperglycemia starting on gestational day 18. Hyperglycemia-induced reductions in insulin-induced AKT phosphorylation localized primarily to fetal skeletal muscle. The skeletal muscle of hyperglycemia-exposed fetuses also exhibited impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…Further, IRS1-PI3K activity, but not IRS1 phosphorylation, was reduced in fetal muscle in offspring of obese sheep (34); although, these measures in fetal sheep were made in fasted, and not insulin-stimulated tissues, it provides additional evidence that IRS1-PI3K may be a critical node regulated by maternal obesity in the fetal muscle. Lastly, reduced insulin-stimulated glucose uptake in fetal muscle has also been found in a rat model of fetal hyperglycemia with impairments in insulin signaling occurring at the level of Akt and not IRS1 (35).…”
Section: Discussionmentioning
confidence: 83%
“…Further, IRS1-PI3K activity, but not IRS1 phosphorylation, was reduced in fetal muscle in offspring of obese sheep (34); although, these measures in fetal sheep were made in fasted, and not insulin-stimulated tissues, it provides additional evidence that IRS1-PI3K may be a critical node regulated by maternal obesity in the fetal muscle. Lastly, reduced insulin-stimulated glucose uptake in fetal muscle has also been found in a rat model of fetal hyperglycemia with impairments in insulin signaling occurring at the level of Akt and not IRS1 (35).…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, it has been shown that fetal hyperglycemia caused by gestational diabetes of the mother causes insulin resistance in developing skeletal muscle (Kua et al, 2019), suggesting that targeting of SDC3 during gestational diabetes might be beneficial to both mother and fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in SDC3 expression have been linked to metabolic syndrome, regulation of energy balance and obesity, all risk factors predisposing to development of type 2 diabetes mellitus (Chang et al, 2018; Strader et al, 2004). Moreover, it has been shown that fetal hyperglycemia caused by gestational diabetes of the mother causes insulin resistance in developing skeletal muscle (Kua et al, 2019). Further work to investigate the role of SDC3/INSR/AKT signaling in a diabetic model would be advantageous to elucidate any protective effects from targeting this pathway on diabetic myopathy as well as on regulation of glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…The body composition of female dams, P21 offspring, and 8W young adult offspring were measured using EchoMRI (EchoMRI LLC, Houston, TX) ( 14 ). Intraperitoneal glucose tolerance testing (GTT) and intraperitoneal insulin tolerance testing (ITT) were performed as published previously ( 14 , 42 ). Briefly, animals were fasted for 5-6 hours prior to GTT, and 2 hours prior to ITT.…”
Section: Methodsmentioning
confidence: 99%